Ruxolitinib does not completely abrogate the functional capabilities of TLR4/9 ligand-activated NK cells - Mestre-Durán, Carmen; Martín-Cortázar, Carla; García-Solís, Blanca; Pernas, Alicia; Pertíñez, Lidia; Galán, Víctor; Sisinni, Luisa; Clares-Villa, Laura; Navarro-Zapata, Alfonso; Al-Akioui, Karima; Escudero, Adela; Ferreras, Cristina; et al. (Frontiers in Immunology, 2023)
Natural killer (NK) cells are lymphocytes from the innate immune system part of the first defense barrier against infected and transformed cells, representing 5%-15% of peripheral blood lymphocytes. The cytotoxic capacity of NK cells is controlled by a balance between inhibitory and activating NK receptors expressed on their surface, which recognize and interact with the ligands on stressed cells. The cytokines involved in NK cell activation, proliferation, survival, and cytotoxicity are signaled mainly through the Janus kinase and signal transducer and activator of transcription proteins (JAK/STAT) pathway. NK cells are also activated in response to pathogens through Toll-like receptors (TLRs) expressed on their surface. Ruxolitinib is a specific JAK1/2 inhibitor approved for treating myelofibrosis and for steroid-refractory acute and chronic graft-versus-host disease (SR-GvHD). This study showed the effects of ruxolitinib on TLR4 and TLR9 ligand-activated NK cells from healthy donors. Ruxolitinib did not completely inhibit STAT3 phosphorylation and had a moderate effect on NK cell cytokine activation via the TLR pathway. Only the highest doses of ruxolitinib led to a decrease in the pro-inflammatory cytokines tumor necrosis factor α, interferon-γ, interleukin-6, and interleukin-1β. The cytotoxic capacity of stimulated NK cells versus K562, SEM, and MV-4-11 cell lines was reduced by increasing doses of ruxolitinib, but it was not completely abolished and we observed no major changes in degranulation capacity. Phenotypic changes were observed in activated NK cells in the presence of ruxolitinib. In a small cohort of pediatric patients treated with ruxolitinib for SR-GvHD, we observed no decrease in NK cell counts; however, further prospective studies with larger cohorts are necessary to confirm this finding. In summary, our results showed that the functional capabilities and phenotype of NK cells activated through TLR4/9 agonists were not completely abolished by the inhibition of the JAK-STAT pathway by ruxolitinib.